Precipitation of carbides in F82H steels and its impact on mechanical strength. (December 2016) - Kano, S.; Yang, H.L.; Suzue, R.; Matsukawa, Y.; Satoh, Y.; Sakasegawa, H.; Tanigawa, H.; Abe, H.
Highlights: The ratio between the volume of precipitate in tempered F82H steel by TEM ( VTEM = 57.6 × 10 – 4 m − 3 ) and extracted residue test ( VTEM = 52.4 × 10 – 4 m − 3 ) was numerically-derived the 1.09. The nucleation barrier of fine particles in F82H which is presumably M23 C6 type particle exited in the TP ranged from 15.2 to 16.2. The quantitatively precipitation strengthening of M23C6 and MX type precipitate (σ PPT, M23C6, σ PPT, MX ) elucidated, the ratio between tensile strength (σ 0.2 ) from precipitation contribution and overall proof strength (σ PPT /σ 0.2 ) was approximately 4–9%. Abstract: The precipitation of carbides in F82H steel and its model steel (Fe-0.2TaC) were investigated by transmission electron microscopy (TEM) and extracted residue tests (ERT). The effects of tempering on the precipitation in F82H steels were elucidated on the basis of the characterization of carbides, as well as the quantitative estimation of precipitation strengthening at room temperature. Firstly, the number density of precipitates was measured by extracted residue test in Fe-0.2TaC and tempered F82H steel, and compared with the TEM observation. It was found that the ratio of volume fraction between the TEM and the ERT was respectively 1.84 and 0.54 for Fe-0.2TaC and tempered F82H steel, revealing that the collection probability of ERT strongly depends on the precipitate features, size and number density. Effects of annealing on the precipitation in F82H steels were investigated by ERT. The amount of carbide showed a non-linear relationship to tempering parameter, TP = T (20 + log t ). It steeply increased in the TP range from 15.3 to 16.2. The precipitation strengthening in F82H steel was estimated to be about 5–10% relative to its proof strength, suggesting that the carbides in F82H steel have a minor role on the tensile strength at room temperature, though these precipitates are greatly beneficial for improving the creep and radiation resistance at elevated temperatures.